Rights-based Claims Made by UK Anti-abortion Activists - Pam Lowe; Sarah-Jane Page (Harvard FXB Center for Health and Human Rights, 2019)
This article analyzes the ways in which rights-based arguments are utilized by anti-abortion activists in the UK. Drawing on an ethnographic study featuring 30 abortion clinic sites, anti-abortion marches, and other campaigns, we argue that rights-based claims form an important part of their arguments. In contrast to the way in which human rights law has been interpreted to support abortion provision, anti-abortion activists seek to undermine this connection through a number of mechanisms. First, they align their arguments with scientific discourse and attempt to downplay the religious motivation for their action. While this is an attempt to generate greater credibility for their campaign, ultimately, the coopting of scientific arguments actually becomes embedded in their religious practice, rather than being separate from it. Second, they reconfigure who should be awarded human rights, arguing not only that fetuses should be accorded human rights but also that providing abortion to women goes against women's human rights. This article is important in showing how rights claims are religiously reframed by anti-abortion activists and what the implications are regarding debates about access to abortion services in relation to religious rights and freedom of belief.